New Generation Hole Transporting Materials for Perovskite Solar Cells: Amide‐Based Small‐Molecules with Nonconjugated Backbones. Issue 32 (8th October 2018) - Petrus, Michiel L.; Schutt, Kelly; Sirtl, Maximilian T.; Hutter, Eline M.; Closs, Anna C.; Ball, James M.; Bijleveld, Johan C.; Petrozza, Annamaria; Bein, Thomas; Dingemans, Theo J.; Savenije, Tom J.; Snaith, Henry; et al.
Abstract: State‐of‐the‐art perovskite‐based solar cells employ expensive, organic hole transporting materials (HTMs) such as Spiro‐OMeTAD that, in turn, limits the commercialization of this promising technology. Herein an HTM (EDOT‐Amide‐TPA) is reported in which a functional amide‐based backbone is introduced, which allows this material to be synthesized in a simple condensation reaction with an estimated cost of <$5 g −1 . When employed in perovskite solar cells, EDOT‐Amide‐TPA demonstrates stabilized power conversion efficiencies up to 20.0% and reproducibly outperforms Spiro‐OMeTAD in direct comparisons. Time resolved microwave conductivity measurements indicate that the observed improvement originates from a faster hole injection rate from the perovskite to EDOT‐Amide‐TPA. Additionally, the devices exhibit an improved lifetime, which is assigned to the coordination of the amide bond to the Li‐additive, offering a novel strategy to hamper the migration of additives. It is shown that, despite the lack of a conjugated backbone, the amide‐based HTM can outperform state‐of‐the‐art HTMs at a fraction of the cost, thereby providing a novel set of design strategies to develop new, low‐cost HTMs. Abstract : In order to reduce the cost of hole transporting materials (HTMs) for perovskite solar cells, the amide‐bond is introduced in the backbone resulting in a straightforward synthesis. Despite the lack of conjugation, the here presented HTM (EDOT‐Amide‐TPA) outperforms state‐of‐the‐art materials in performance, showing over 20% power conversion efficiency, and stability, which is assigned to the unique properties of the amide‐bond.